ANALISIS STRATEGI PEMASARAN MENGGUNAKAN ANALISIS SWOT DAN QSPM - Wahdah, Ajeng Anis; Hapsari, Radhita Dwi Vata (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
One of the small things that can be done to reduce the negative effects of fast fashion on the environment is purchasing used goods. However, there are many companies engaged in used-goods sales do not survive; the dominating cause is failure in choosing marketing strategies. In order to avoid similar unwanted results, Twice Looker, a thrift shop business, needs to strengthen its marketing plan to create long-term business growth using SWOT and QSPM analyses. This descriptive case study uses primary data, acquired from interviews and documentation, and secondary data in forms of business documents and journals. They were analyzed using IFE Matrix, EFE Matrix, SWOT Matrix, and QSPM. The results indicate that Twice Looker is on the fifth quadrant, which suggests the use of hold-and-maintain strategy, market penetration, and product development. Further, the results of the QSPM indicate that market penetration strategy is the most appropriate alternative, with the TAS value of 5.12. therefore, the management of Twice Looker are advised to enhance their marketing by formulating online sales promotion planning and to consistently conducting and continuing the said promotion.